1866 Ala. Pen. Code 63 - (:unkn) unknown (My University, 1866)
§ 204: Prohibited selling, giving, or lending any pistol, Bowie-knife, or other knife of like kind to a minor under eighteen years of age. Violators fined not less than fifty nor more than five hundred dollars.
Keywords: TRANSFER - MINORS